Grant - Chernow, Ron (Penguin Press, 2017)
"Pulitzer Prize-winner and biographer of Alexander Hamilton, George Washington, and John D. Rockefeller, Ron Chernow returns with a sweeping and dramatic portrait of one of our most compelling generals and presidents, Ulysses S. Grant. Ulysses S. Grant's life has typically been misunderstood. All too often he is caricatured as a chronic loser and inept businessman, fond of drinking to excess; or as the triumphant but brutal Union general of the Civil War; or as a credulous and hapless president whose tenure came to symbolize the worst excesses of the Gilded Age. These stereotypes don't come close to capturing adequately his spirit and the sheer magnitude of his monumental accomplishments. A biographer at the height of his powers, Chernow has produced a portrait of Grant that is a masterpiece, the first to provide a complete understanding of the general and president whose fortunes rose and fell with dizzying speed and frequency. Before the Civil War, Grant was flailing. His business ventures had been dismal, and despite distinguished service in the Mexican War, he ended up resigning from the army in disgrace amid recurring accusations of drunkenness. But in the Civil War, Grant began to realize his remarkable potential, soaring through the ranks of the Union army, prevailing at the Battle of Shiloh and in the Vicksburg campaign and ultimately defeating the legendary Confederate general Robert E. Lee after a series of unbelievably bloody battles in Virginia. Along the way Grant endeared himself to President Lincoln and became his most trusted general and the strategic genius of the war effort. His military fame translated into a two-term presidency, but one plagued by corruption scandals involving his closest staff. All the while Grant himself remained more or less above reproach. But, more importantly, he never failed to seek freedom and justice for black Americans, working to crush the Ku Klux Klan and earning the admiration of Frederick Douglass, who called him 'the vigilant, firm, impartial, and wise protector of my race." After his presidency, he was again brought low by a trusted colleague, this time a dashing young swindler on Wall Street, but he resuscitated his image by working with Mark Twain to publish his memoirs, which are recognized as a masterpiece of the genre. With his famous lucidity, breadth, and meticulousness, Chernow finds the threads that bind these disparate stories together, shedding new light on the man whom Walt Whitman described as "nothing heroic... and yet the greatest hero." His probing portrait of Grant's lifelong struggle with alcoholism transforms our understanding of the man at the deepest level. This is America's greatest biographer, bringing movingly to life one of our finest but most underappreciated presidents. The definitive biography, Grant is a grand synthesis of painstaking research and literary brilliance that makes sense of all sides of Grant's life, explaining how this simple Midwesterner could at once be so ordinary and so extraordinary"--